In Praise of Getting Lost: Sven Hedin and the Lowline - James Ramsey (Oz, 2013)
This article represents Ramsey's design for the Lowline, a vast underground reuse of New York’s abandoned trolly terminal on the Lower East Side. It is partly inspired by notes from Sven Hedin’s celebrated expedition into Central Asia in the early 1900s.